Flexible experimental platform for dispersion-free temporal characterization of ultrashort pulses - Rupprecht, Patrick; Magunia, Alexander; Aufleger, Lennart; Ott, Christian; Pfeifer, Thomas (Optics express, 2023)
The precise temporal characterization of laser pulses is crucial for ultrashort applications in biology, chemistry, and physics. Especially in femto- and attosecond science, diverse laser pulse sources in different spectral regimes from the visible to the infrared as well as pulse durations ranging from picoseconds to few femtoseconds are employed. In this article, we present a versatile temporal-characterization apparatus that can access these different temporal and spectral regions in a dispersion-free manner and without phase-matching constraints. The design combines transient-grating and surface third-harmonic-generation frequency-resolved optical gating in one device with optimized alignment capabilities based on a noncollinear geometry.